So Easy to Write a Story with a Mind Map: An Experimental Study - Uysal, Hümeyra; Sidekli, Sabri (GIST – Education and Learning Research Journal, 2024)
This study aimed to determine the effect of mind mapping on story writing skills of the students.A pre-test, a post-test, and a semi-experimental research design were used in this study. The study group consisted of a total of 86 third-grade students; 33 students from the experimental group, 23 students from the control 1 group, and 30 students from the control 2 groups. Stories were written by the students in the experimental group by using the mind map method during 18 lesson hours. In the control 1 group, story topics were given to the students, and they were asked to write stories about them as homework during one lesson hour for 9 weeks. In the control 2 group, the researcher did not intervene in their lessons during the term. As a result of the research, there was an increase in the post-test writing skill scores of the experimental and control 1 groups. The mind map method and story writing with homework exercises improved students’ writing skills.